2002
DOI: 10.1080/073993302760190100
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Educational Program for Premenstrual Syndrome on Women of Korean Industrial Districts

Abstract: The purpose of this study is to find an intervention that will help alleviate women's signs and discomforts associated with premenstrual syndrome (PMS). As the social activities of women increase, eliminating PMS becomes increasingly important for many Korean women. A possible health care countermeasure for PMS is to assess PMS at an early stage; clarify the premenstrual signs, symptoms, and tensions; and afterward alleviate the premenstrual signs and discomforts. Related educational programs have been found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…The results of this study indicate education regarding PMS and related subjects can change self‐care skills, which were supported by studies of Taylor (1999), Chau & Chang (1999) and that of Min (2002). All these studies aimed to assess the effectiveness of similar interventions through educational or CBT on PMS and related symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study indicate education regarding PMS and related subjects can change self‐care skills, which were supported by studies of Taylor (1999), Chau & Chang (1999) and that of Min (2002). All these studies aimed to assess the effectiveness of similar interventions through educational or CBT on PMS and related symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Several previous reports have noted the beneficial effects of educational programs on premenstrual symptoms. 9 , 10 The present study differs from these studies because we showed education had a preventative effect on PMS/PMDD progression.…”
Section: Discussioncontrasting
confidence: 82%
“…Disasters such as major earthquakes cannot be predicted, so it is necessary to explore preventive measures for PMS/PMDD on a routine basis. Several previous studies have noted the beneficial effects of educational programs on PMS/PMDD, 9 , 10 but there are few data about whether educational programs can prevent disaster-induced PMS/PMDD. This study used data from our previous school-based study to further investigate the effect of educational programs on PMS/PMDD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore graded activity, especially aerobic exercise and fitness training, seem to have a beneficial effect on premenstrual symptoms [25,26]. Two controlled trials demonstrated a significant decrease inpremenstrual symptoms in a group of women with PMS who had received an educational program combining psychoeducation about basic menstrual cycle physiology and a session of training in self-care behaviors [27,28].…”
Section: Treatment Of Premenstrual Syndromementioning
confidence: 99%